Analisis Pendapatan Usahatani Kacang Merah Berdasarkan Status Kepemilikan Lahan Di Desa Tempok Kecamatan Tompaso Kabupaten Minahasa - Manopo, Veronika Maria; Baroleh, Jenny; Rori, Yolanda Pinky Ivanna (AGRI-SOSIOEKONOMI, 2024)
The aim of the research is to analyze red bean farming income based on land ownership status in Tempok Village, Tompaso District, Minahasa Regency. The research took place from June to August 2023. The data used in the research were primary data obtained from direct interviews with red bean farmers using questionnaires, and secondary data obtained from research results and journals. Sampling used a purposive sampling method, namely farmers were selected based on the last harvest in May and June, and the samples were divided into three categories, namely farmers who own their own land, farmers who rent land, and sharecroppers who work on other people's land. The number of respondents was 12 red bean farmers consisting of 4 owner farmers, 4 tenant farmers and 4 sharecroppers. The data collected was analyzed descriptively using farming income analysis. The results of the research show that red bean farming income is based on land ownership status, namely: owner farmers amounting to IDR49.129.667, tenant farmers amounting to IDR41.991.500, and sharecroppers amounting to IDR25.925.000 per planting season.